Short-Term Effects of Focal Muscle Vibration on Motor Recovery After Acute Stroke: A Pilot Randomized Sham-Controlled Study - Toscano, Massimiliano; Celletti, Claudia; Viganò, Alessandro; Altarocca, Alberto; Giuliani, Giada; Jannini, Tommaso B.; Mastria, Giulio; Ruggiero, Marco; Maestrini, Ilaria; Vicenzini, Edoardo; Altieri, Marta; Camerota, Filippo; et al. (Frontiers in Neurology, 2019)
Repetitive focal muscle vibration (rMV) is known to promote neural plasticity and long-lasting motor recovery in chronic stroke patients. Those structural and functional changes within the motor network underlying motor recovery occur in the very first hours after stroke. Nonetheless, to our knowledge, no rMV-based studies have been carried out in the acute stroke patients so far, and the clinical benefit of rMV in this phase of stroke is yet to be determined. The aim of this randomized double-blind sham-controlled study is to investigate the short-term effect of rMV on motor recovery in acute stroke patients. Out of 22 acute stroke patients, 10 were treated with the rMV (vibration group - VG), while 12 underwent the sham treatment (control group - CG). Both treatments were carried out for three consecutive days, starting within 72 hours of stroke onset; each daily session consisted of three 10-minute treatments (for each treated limb), interspersed with 1-minute interval. rMV was delivered using a specific device (Cro®System, NEMOCO srl, Italy). The transducer was applied perpendicular to the target muscle’s belly, near its distal tendon insertion, generating a 0.2–0.5-mm peak-to-peak sinusoidal displacement at a frequency of 100 Hz. All participants also underwent a daily standard rehabilitation program. The study protocol underwent local ethics committee approval (ClinicalTrial.gov NCT03697525). Written informed consent was obtained from all of the participants. With regard to the different pre-treatment clinical status, VG patients showed significant clinical improvement with respect to CG-treated patients among the NIHSS (p<0.001), Fugl-Meyer (p=0.001), and Motricity Index (p<0.001) scores. In addition, when the upper and lower limb scales scores were compared between the two groups, VG patients were found to have a better clinical improvement at all the clinical end points. This study provides the first evidence that rMV is able to improve motor outcome in a cohort of acute stroke patients regardless of the pretreatment clinical status. Being a safe and well-tolerated intervention which is easy to perform at bedside, rMV may represent a valid complementary nonpharmacological therapy to promote motor recovery in acute stroke patients.